Permit Simplification for Upstream Oil and Gas Operation in Indonesia: The Development Administration and Good Governance Perspectives - Didik Sasono Setyadi; Hyronimus Rowa; Ario Bimo Utomo (Eduvest - Journal of Universal Studies, 2023)
According to the Indonesian Constitution, any Vital and Strategic Sectors for the People's Interests have to be managed by the State. Oil and Gas until now are two of the Strategic and Vital Business Sectors in Indonesia. Therefore Indonesia establishes an institution namely the Special Task Force of Executive Oil and Gas Business Activity (SKK Migas). SKK Migas deals with Production Sharing Contracts with Exploration and Exploitation (Upstream) Oil and Gas Companies. In its activities, there are many regulations apply and required to obtain permits. The current problem nowadays are related to the type of the permits, the regulations and procedures to follow, as well as institutions/permit issuers to deal with are too many so that the permit system for Upstream Oil and Gas have caused handicaps for the industry to grow competitively. While on the other hand Indonesia still has a high dependency on Oil and Gas Industry for State Income reason and Energy Resilience. The old paradigm of the bureaucracy system in one the most causes of inefficiency and ineffectiveness of bureaucracy in Indonesia. Even though the reformation has been started since 1998 however the change of old bureaucratic system and mentality of the bureaucrats into the new paradigm of good governance is still very less and tend to be progressing very slowly. Overlapping and redundancies of regulations, authorities have caused Indonesia is less competitive destination comparing to the neighboring countries in attracting foreign investment.